Indoor air quality (IAQ) characteristics and its microbial community identifications at two selected schools in Pahang, Malaysia: a preliminary study - Ariffin, Hizzri; MG, Zati Nabilah; Zaidi, Nurul Amni; N, Shahida; Zahaba, Maryam; Abdul Hadi, Hazrin; Sharif, Mohd. Faez; Mohd Aris, Mohd Shukri (Asian Journal of Agriculture and Biology (AJAB), 2018)
It is important to assess IAQ characteristics and to identify possible microbial contaminants in schools’ indoor environment because children are more vulnerable to air pollutants as they inhale more air pollutants per kilograms of body weight. Hence, this study aims to assess and to compare the level of selected IAQ parameters and microbiological contaminants inside the classroom of schools in urban area and rural area during occupied and non-occupied period. This study also aims to identify airborne bacteria species and fungi genera within classroom of schools in those area. For methodology of the study, schools were selected based on their location. School X (SX) was located in Kuantan, Pahang, while school Y (SY) was located in Pekan, Pahang. The physical IAQ parameters (Temperature, Relative Humidity (RH), Carbon Dioxide (CO2) were measured using VelociCalc® Multi-Function Ventilation Meter 9565 (TSI®, Minnesota, USA), and airborne particulate matter (PM) were measured using DustMate (Turnkey Instruments, UK). Surface Air System Indoor Air Quality (SAS IAQ), (PBI International, Italy) was used to collect the microbial contaminants and subsequently CFU were counted. The data were recorded for 30 minutes for each time-slot for 8 hours during occupied and non-occupied period within selected classrooms. Bacteria identification was done using 16S rRNA gene sequence analysis and fungi were identified macroscopically through direct identification technique up to genus level. The results were compared to standard reference limit based on Industrial Code of Practice on Indoor Air Quality (ICOP, 2010) regulated by the Department of Occupational Safety and Health (DOSH, 2005). This study found that temperature (SX, Occupied; 34.9±3.9, Non-Occupied; 32.8±0.7), (SY, Occupied; 30.7±0.2, Non-Occupied; 30.6±0.5), RH (SY, Occupied; 74.4±2.9, Non-Ocupied; 70.05±1.0) and bacterial CFU counts (SX, Occupied; 558±308), (SY; Occupied; 903±415, Non-Occupied; 1176±303) exceeded the standard limit regulated by DOSH. Number of gram-negative bacteria dominated over gram-positive bacteria in both settings. Bacillus sp. (B. atrophaeus, B. subtilis, B. pumilus, B. altitudinis. B. tequilensis, and B. aerophilus) were the most dominant species, followed by Staphylococcus sp. (S. warneri, S. sciuri, S. haemolyticus, and S. gallinarum). The common fungal species isolated in both schools during occupied and non-occupied period were Aspergillus, Alternaria, Cladosporium, Penicillium, and Mucor.